Intensification of zinc dissolution process in sulphuric acid - Stanojević D.; Tošković D.; Rajković M.B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Many high purity salts are produced by dissolving pure metal in non-oxidizing mineral acids. If hydrogen overpotential on the given metal is high, then the rate of overall process is defined by reaction of hydrogen ion reduction. This study investigated the possibility of accelerated dissolving of metal zinc in sulphuric acid by introducing copper cathode on which evolving hydrogen is much easier than on zinc. It was found out that the acceleration of zinc dissolving is possible and, at constant surface of copper cathode depends on the quality of electrical contact between copper electrode and zinc.